Rationale and design for efficacy and safety evaluation of Bone-Anchored Maxillary Protraction (BAMP) for patients with unilateral cleft lip and palate with skeletal anterior crossbite: a single-arm, open-label, non-randomised prospective study protocol. Issue 9 (1st September 2022) - Shimada, Eriya; Kanetaka, Hiroyasu; Yamauchi, Kensuke; Takahashi, Tetsu; Nochioka, Kotaro; Igarashi, Kaoru
Abstract : Introduction: Bone-anchored maxillary protraction (BAMP) was devised recently as a method of direct maxillary protraction using anchor plates implanted in the maxilla and mandible without involving the teeth. Although several reports have described orthognathic effects of BAMP on patients with cleft lip and palate (CLP) with skeletal crossbite, none has described a study of Japanese patients with CLP or of BAMP treatment effects on speech in patients with CLP. This study, by performing BAMP treatment, and by evaluating speech function and skeletal and soft tissues, is intended to clarify BAMP efficacy and safety for patients with unilateral CLP (UCLP) who have skeletal crossbite. Methods and analysis: This single-arm, open-label, non-randomised prospective study examines 20 patients with UCLP with skeletal crossbite (Wits appraisal ≤−5.0 mm). These 10–15 year-old participants had already undergone cheiloplasty, palatoplasty and bone grafting. The anchor plates are implanted in the zygomatic process in the maxilla and in the anterior part of the mandible. Two weeks after anchor plate implantation, maxillary protraction is started using elastics. Protraction is performed at 150 g per side at the start of protraction, 200 g per side from 1 month after the start of protraction and 250 g per side from 3 months after the start of protraction. The treatment period will be approximately 1½ years. Pretreatment and post-treatment, cephalometric analysis, speech evaluation, nasopharyngeal closure function evaluation and facial soft tissue evaluation will be performed to ascertain the effects of BAMP on patients with UCLP. Ethics and dissemination: Ethical approval for this study has been received from Tohoku Certificated Review Board of Tohoku University, Japan, CRB2200003. The approval number is 2021-34-2. The results of this research shall be presented at domestic and international academic conferences, and be published to peer-reviewed journals. Trial registration number: jRCTs022210007.